Family practice in Turkey: Observations from a pilot implementation. (2nd January 2016) - Yaman, Hakan; Güneş, Evrim Didem
Abstract: Objective : Turkey has implemented family practice on a pilot basis as part of the reform in health care, since 2005. This paper aims to understand and describe the prevalent practice patterns and clinic characteristics during the transition period.Design : A cross-sectional descriptive study design was used.Subjects : An online survey was conducted among Turkish GPs working as primary care doctors (without vocational training) during the reform period. Clinic and GP characteristics are analysed with descriptive statistics.Results : List size is an important factor; larger lists lead to shorter consultation time and a longer wait for patients. GPs are generally satisfied with the reform.Conclusion : During the transition to family practice access of patients to health care has improved and GPs are satisfied with their job. key points: Patients in Turkey have adequate access to primary health care services. The waiting time for consultation is relatively short. Basic prevention activities occupy the majority of the GPs' time. Reducing the panel size and introducing appointment systems may be useful.